Magnetic susceptibility of n- and p-Si single crystals containing thermodonors - Babich, V.М.; Luchkevych, M.M.; Tsmots, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Using a series of experimental methods (Hall effect, electron paramagnetic resonance and magnetic susceptibility (MS, χ)) comparison has been made for the kinetics of formation inherent to different types of thermodonors (TDs) (doubly-charged and shallow ones) under thermal treatments (TT) at 450 °C with the kinetics of paramagnetic center accumulation in the samples obtained by the MS method. The absence of correlation between these dependences has been shown. The dependences χ(H) obtained both at 300 and 77 K that have orientation and paramagnetic component determine neither of these two kinds of TD-centers as it was in the case of 450 °C TT for p-Si(B) samples where the χ par component is determined by the concentration of deep TDs (Еі ≥ 0.2 еV). The χ(H) value in the n-Si(P) samples after TT at 450 °C is determined, evidently, by intermediate non-stable complexes, as well as by those formed during rapid cooling the samples